Saharan, Aral-Caspian and Middle East dust travels to Finland (1980–2022) - Varga, György; Meinander, Outi; Rostási, Ágnes; Dagsson-Waldhauserova, Pavla; Csávics, Adrienn; Gresina, Fruzsina (Pergamon., 2023)
Studies on atmospheric dust and long-range transport of mineral dust have been a focus of atmospheric science in recent years. With its wide range of direct and indirect effects, mineral dust is one of the most uncertain elements in the mechanisms of climate change, and a deeper understanding of its role is essential for understanding future processes. The aim of our research was to provide the first systematic data on the so far episodically documented northward transport mineral dust from arid-semiarid areas. So, in this paper, we present dust storm events from lower latitudes reaching the Finnish atmosphere, based on the MERRA-2 model Dust Column Mass Density data and after a multistep verification procedure using independent data source. In total, 86 long-range dust storm events were identified between 1980 and 2022, when air masses loaded with dust reached Finland. Based on backward-trajectories different sources were identified: 59 were Saharan, 22 were Aral-Caspian, and five were associated with Middle Eastern source areas. Considerable variation in inter-annual frequencies was observed among the source areas, which may be due to changes in circulation conditions and the effects of human activity (agriculture and land use changes in Aral Sea region). There is a clear maximum of dust events in spring (60%), followed by summer and autumn (where 10 of the 11 autumn episodes were from the Sahara). However, the number and proportion of scarce winter events have more than doubled since 2010 compared to the preceding 30 years, but no autumn events were registered during this period. This clear temporal variation coincides with changes in dust transport observed in other regions of Europe, driven by greater atmospheric meridionality associated with climate change and driven by reduced temperature difference between low and high latitudes due to enhanced temperature increases at Arctic regions.